THE EFFECT OF DIFFERENCES IN TAX BOOKS ON INCREASES IN CORPORATE INCOME - Hastuti, Rini Tri; Nariman, Augustpaosa; Ardhiansyah3, Ardhiansyah; Agatha, Monica (International Journal of Application on Economics and Business, 2025)
The goal to be achieved by conducting this research is to find out whether differences in tax books have an effect on profit growth proxied by fixed differences and temporary differences with the research subjects, namely corporations with the consumer goods industry sector listed on the IDX in the 2019-2021 range. The sample selection was carried out by purposive sampling method and then 34 corporations that met the criteria were selected. The research data was processed using multiple linear regression analysis using the Eviews 12 program. From the research that has been done, it can be concluded that fixed differences and also temporary differences which are proxies for differences in tax books have no effect on profit growth. The results of this research have implications that the increase in income generated by corporations from time to time is a pure result of the operational performance of corporations and is not affected by differences in tax books.